SPEECH ACT ANALYSIS OF TEACHER TALK IN EFL CLASSROOM - Santosa, Aulia Wahyu; Kurniadi, Arik (Jurnal Penelitian Humaniora, 2020)
The speech act used in EFL classroom may lead to understanding or misunderstanding due to the distinct cultures between the origin of language and the users. The objective of the research were to find out speech act classification mostly used by an EFL teacher while teaching, the reason of why certain classification was preferred and the implication of the selected speech act classification toward the teaching and learning process. This research was a case study research involving an English teacher teaching an EFL class. The study uses Searle’s framework of speech act classification as the instrument. The findings of the research showed the frequency of each classification found as the following: 57% for assertive, 25 for expressive, 40% for directive, and 1% for commissive. Assertive speech acts were used mostly by the teacher because the teacher gived the students test practice and discussed it later on. The study concluded that the choice of speech acts classification determined the teaching approach and vice versa.